Effectiveness of Microteaching in Improving Basic Life Support Knowledge at SMK Pawiyatan Surabaya - Lyndia Effendy; Natalia Yuwono; Maria Jessica Rachman; Arief Gunawan Darmanto (Jurnal Medika: Medika, 2025)
Background: Basic Life Support (BLS) skills are vital competencies that are often under-trained among adolescents due to time constraints in education. As an active demographic group, teenagers are vulnerable to emergency situations, making efficient and effective training essential. Objective: To measure the effectiveness of a 10-15 minutes BLS microteaching intervention combined with hands-on practice in improving the knowledge and skills of vocational high school (SMK) students at SMK Pawiyatan Surabaya. Methods: This study used a pretest-posttest design. The intervention was conducted from February 2024 at SMK Pawiyatan Surabaya, involving 147 tenth-grade students from various majors. The session included a 10-15 minutes microteaching module, live demonstrations, and hands-on practice using QCPR manikins. Student knowledge was assessed through questionnaires before and after the intervention. Results: The average knowledge score increased from 58% (pretest) to 85% (posttest), showing a 27% improvement. 78% of participants achieved technical competency in chest compressions according to AHA standards. Conclusion: A 10-15 minutes BLS microteaching session proved effective in enhancing vocational students' knowledge and skills. This approach is recommended for integration into school curricula as an efficient emergency health education strategy.